SMART-TECHNOLOGIES IN BUSINESS ACTIVITIES - MOZGOVYI, Ievgen (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the role and impact of SMART-technologies on entrepreneurial activity, focusing on their ability to automate processes, reduce costs, and improve the accuracy and speed of decision-making. The number of business entities is analyzed and it is proved that their number is decreasing annually, since business operates in conditions of uncertainty, has constant losses, growth of receivables and payables, which subsequently leads to their bankruptcy and liquidation.The advantages of implementing SMART technologies, including their positive impact on the efficiency of management processes and customer interaction, are presented. It is also proved that the use of Smart technologies in business activities provides: improved business management; cost reduction; increased productivity and efficiency; improved customer service; innovation and competitive advantages; and data security and protection.SMART-technology involves the use of computer systems and microprocessors to perform daily tasks and exchange information. Thus, smart technologies are widely used in various sectors of the economy, including entrepreneurship, becoming the basis of the smart economy. The article discusses the main challenges faced by enterprises in integrating SMART-technologies, such as high initial costs, the need for specialized knowledge and adaptation of existing business processes. Particular attention is paid to the impact of the war on business in Ukraine, where SMART technologies can help overcome the difficulties associated with the destruction of infrastructure, shortage of resources and reduced purchasing power of the population. The article emphasizes the importance of innovative solutions to ensure business sustainability and efficiency in a rapidly changing environment and crisis situations. The introduction of SMART-technologies is seen as a key factor for increasing competitiveness and adapting business to new conditions
Keywords: SMART-technologies; business entities; business activity; development strategy; management